Characterization and optimization of oil palm empty fruit bunch-glass fibre reinforced recycled polypropylene hybrid composites - Rivai, Makson (2013)
The tremendous utilization of plastics over last decades has led to the environmental problems due to non degradability of plastics. This lead to the development of the composites using natural fibre and plastic. The present study deals with the utilization of empty fruit bunch of oil palm (EFB), glass fibre, as fibre, recycled polypropylene and coupling agent [maleic anhydride grafted polypropylene (MAPP) and fusabond] as composites material. EFB fibres were treated with alkali treatment with conventional, homemade, microwave and ultrasonic methods. Blending of composite material was carried out using twin-screw extruder followed by injection moulding to produce specimens. Characterization of hybrid composites was then carried out to examine the alkali treatments and composition interactions. Fresh and sea water hygrothermal ageing test was performed at 27°C, 60 and 80°C. Accelerated weathering tests was conducted up to 1200 hours while natural weathering test was implemented for more than one year under natural weathering conditions. Tensile testing, FTIR analysis, melt flow index (MFI) analysis, thermo gravimetric analyser (TGA) test, differential scanning calorimetric (DSC) test, water absorptions, and scanning electron microscopy (SEM) were performed to examine the changes of hybrid composites during treatments. Results show that Ultrasonic EFB treatment has the highest properties' stability and rapid treatment compared to modified microwave, homemade alkali treatment and conventional treatment. Homemade alkali treatment provided low-cost and less amount of NaOH is needed. Compounding process, coupling agent, temperature treatments, soaking time, NaOH % and fibre ratio have an important role to offer optimum of physical and mechanical properties and hybrid composite's stability. Natural weathering has small degradation and has similar effects with accelerated weathering test. Results of accelerated weathering and hygrothermal ageing test shown the capabilities on enhancing properties of composites in specific harsh natural environment or marine application. Optimization was done using Response Surface Methodology (RSM) with tensile strength, modulus, elongation at break, and melt flow indexes as the dependent variables (responses) while the parameter of alkali treatment, coupling agent, fibre ratio and compounding process as the independent variables.The experimental results indicate that the proposed mathematical models could adequately describe the performance indicators within the limits of the factors being investigated.